PROBLEMATIKA MEDIASI PERKARA PERCERAIAN BERDASARKAN PENGALAMAN HAKIM MEDIATOR PADA PENGADILAN AGAMA SINGKAWANG - Khairunisa, Tika; Haliyah, Dahlia; Fadhil, Moh. (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
The implementation of the study has some purpose of knowing: 1) How mediator’srole in the divorce mediation at Singkawang Religious Court. 2) How the successrate of the divorce mediation at Singkawang Religious Court. 3) What are theobstacle factors for mediator judges in the divorce mediation at SingkawangReligious Court. This study used empirical normative legal research (applied lawresearch). In addition uses a descriptive qualitative approach. This study uses twodata sources, there are primary data sources obtained from research subjects, as wellas secondary data sources consisting of primary and secondary legal materials. Thisstudy uses structured interview techniques and documentation. Data analysistechniques uses are reduction, presentation then verification the data. Then, usedtechnique of rechecking all of the data and information (member check) obtainedfrom the data collected. Through the findings obtained from the results of theanalysis of data that have been studied in this study, it can be concluded that: 1)Mediator judges in carrying out his role to reconcile the parties in divorce mediationat Singkawang Religious Court following Supreme Court Regulation Number 1 of2016 on Mediation Procedures. However, the final mediation is entirely based onthe parties’ will. 2) The success rate of mediation at Singkawang Religious Courtis low. 3) Factors that inhibit mediators in mediation at Singkawang Religious Courtare difficulty of reconciling the parties who have complicated problems in thehousehold, the absence of either litigant, the absence of goodwill of the parties orone party, the parties strong desire to divorce and position of the judge as a mediatorcauses a limited quantity of mediators.